Financial Stability and Fiscal Crises in a Monetary Union - Jahjah, Samir (IMF Working Papers; Working Paper, 2001)
The main tasks of central banks are to secure price and financial stability. These objectives can, in times of crises, conflict with one another, and the central bank may have to renounce one of them in order to secure the other. In a monetary union, this trade-off can be exacerbated by the presence of highly indebted countries or by the risk of loose fiscal policies. This paper offers a simple theoretical model that captures the trade-off. Different fiscal institutions are compared in order to evaluate their impact on the conduct of monetary policy. More specifically, the fiscal criteria of the Maastricht Treaty and the Pact for Stability and Growth in Europe are analyzed in light of this model. Fiscal mechanisms exist to help prevent or minimize the risk of fiscal crises and the corresponding risk of central bank financing and inflation.